(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
This article proposes the usage of the concept of testimony as an analytical category from the point of view of the history of the present time and, specifically, while working with oral history. First, I will consider testimony as an act and then an object. Next, the movement from act to object will allow us to identify how memory becomes an object of study in history. Therefore, testimony could be an analytical category that can establish bridges between the interpretation of memories and historiography. As an example, I will do a brief exercise with oral testimonies done with peasants in Mexico.